FACTORS INFLUENCING FARMERS’ DECISION TO INCREASE BEEF CATTLE BUSINESS SCALE IN CENTRAL JAVA PROVINCE - Roessali, W.; Masyhuri, M.; Nurtini, S.; Darwanto, D.H. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
The purpose of this research was to analyze factors influencing farmers' decision to increasebeef cattle business scale through improved technology. The research was conducted by using a surveymethod. Five districts were purposively selected in three base areas and two non-base areas of beefcattle in Central Java Province, Indonesia. Twenty beef cattle groups were selected based on the largestcattle population managed and their performance, while 196 respondents were randomly selected.Farmers’ decision to increase beef cattle business scale was determined using a probit model. Result ofthe research indicated that the number of family labor and expectation to increase income had asignificantly positive influence on the farmers’ decision to increase beef cattle business scale. It meantthat if the total number of family labor increased, so did the farmers’ decision to increase the beef cattlebusiness scale. Also, if the expectation to revenue increased, so did the farmers’ decision to increase thebeef cattle business scale. On the contrary, education level and business risk had negative significantinfluence on the farmers’ decision to increase the beef cattle business scale with the significance levelsof 1.1 and 0.84, respectively.